1921
DOI: 10.2307/1536737
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the Larvæ of Corethra Punctipennis Say

Abstract: INTRODUCTION. 1 Notes from the Biological Laboratory of the Wisconsin Geological and Natural History Survey No. XXI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1932
1932
1985
1985

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Eggleton (1932) learned that the larvae migrate to the surface in the evening during the summer and back to the bottom later the same night in several depressions of Douglas Lake, Michigan. This confirmed Juday's (1921) work on Lake Mendota, Wisconsin, and the same behavior has been reported by other authors. Bluegills are sight-feeders and for this reason they do not feed extensively at night, yet the Ghoaborus movement upward begins about 4:00p.m.…”
Section: Totalsupporting
confidence: 92%
“…Eggleton (1932) learned that the larvae migrate to the surface in the evening during the summer and back to the bottom later the same night in several depressions of Douglas Lake, Michigan. This confirmed Juday's (1921) work on Lake Mendota, Wisconsin, and the same behavior has been reported by other authors. Bluegills are sight-feeders and for this reason they do not feed extensively at night, yet the Ghoaborus movement upward begins about 4:00p.m.…”
Section: Totalsupporting
confidence: 92%
“…Some workers (Wood, 1956) have found Chaoborus both limnetic and benthic in the same lake, but most workers have found Chaoborus to be benthic. Juday (1921) suggested that since Chaoborus are excellent fish food, they avoid fish by burrowing in the bottom mud. However, Chaoborus live in the bottom mud of holomictic lakes when the oxygen and carbon dioxide tensipns are highly unfavorable for fish.…”
Section: Discussionmentioning
confidence: 99%
“…When Chaoborus were put in water with high activity, they did not lose as much activity as Chaoborus put in activityfree water (Table VIIB). Juday (1921) stated that the great abundance of.Chaoborus punctipennis makes it a very important factor in the biological complex of a lake. Chao borus are tolerant of extreme conditions (Eggleton, 1931) an d often are the ■ only important macroscopic benthic organisms.…”
Section: Size Of the Chaoborus Population And Its Capability For Tranmentioning
confidence: 99%
“…Daily Activity of Chaoborid Larvae Juday (1921) reported that an average of 33 percent of the benthic larvae became planktonic each night, whereas Wood (1956) stated that 22 percent became planktonic . These percentages were based on the ratio of larvae collected from the plankton at peak activity to the total number of benthic larvae .…”
Section: A Population Interactionmentioning
confidence: 99%
“…This can only be demonstrated when members of a population are studied individually . Some authors (Juday, 1921 ;Berg, 1937 ;Lindquist & Roth, 1950 ;Wood, 1956 ;and Malueg, 1966) assume an annual periodicity in the percentage of the benthic larvae that leave the sediments each night . Parma (1971) demonstrated this in laboratory experiments involving individual larvae .…”
Section: A Population Interactionmentioning
confidence: 99%